Technology of Perspective Scanning Methods for Realization of 3D Models of Manufacturing Devices - Novak-Marcincin, Jozef; Torok, Jozef; Barna, Jozef; Novakova-Marcincinova, Ludmila (Manufacturing Technology Journal, 2012)
This article provides perspective into creation of virtual 3D models of manufacturing devices and optimization of existing machine tools by using an alternative scanning device and freeware software applications (open source elements). This alternative offers scans of components surfaces that are from the viewpoint of precision and quality comparable with much more expensive devices. Various parts of the paper describe the process of creation of the environment with the use of Kinect scanner device and various software tools. At the end an additional options are provided for using with sensing device.
Keywords: 3D scanner; digitization; Kinect device